2009
DOI: 10.1016/j.brainres.2008.12.076
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant functional connectivity in autism: Evidence from low-frequency BOLD signal fluctuations

Abstract: A number of recent studies have examined functional connectivity in individuals with Autism Spectrum Disorders (ASD), generally converging on the finding of reduced interregional coordination, or underconnectivity. Underconnectivity has been reported between many brain regions and across a range of cognitive tasks, and has been proposed to underlie behavioral and cognitive impairments associated with ASD. The current study employed functional connectivity MRI (fcMRI) to examine interregional correlations of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
126
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(147 citation statements)
references
References 81 publications
21
126
0
Order By: Relevance
“…Increased activation in associative cortex regions involved in higher order sensory processing has been found in ASC individuals in the visual domain (Samson et al, 2012), while increased functional connectivity between frontal areas (Noonan et al, 2009) and between posterior cingulate and medial temporal cortex (Monk et al, 2009) has been found using fMRI. In synesthesia, the parietal cortex especially has been found to be hyperactivated in different types of synesthesia and this region has also been found to be more strongly connected to the sensory areas involved in inducer-and concurrent processing , supporting the idea of top-down modulation of sensory areas by this higher-order associative region.…”
Section: Discussion Relation Between Synesthesia and Ascmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased activation in associative cortex regions involved in higher order sensory processing has been found in ASC individuals in the visual domain (Samson et al, 2012), while increased functional connectivity between frontal areas (Noonan et al, 2009) and between posterior cingulate and medial temporal cortex (Monk et al, 2009) has been found using fMRI. In synesthesia, the parietal cortex especially has been found to be hyperactivated in different types of synesthesia and this region has also been found to be more strongly connected to the sensory areas involved in inducer-and concurrent processing , supporting the idea of top-down modulation of sensory areas by this higher-order associative region.…”
Section: Discussion Relation Between Synesthesia and Ascmentioning
confidence: 99%
“…Every patient was examined for axis-I co-morbidity by using the German version of the Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I) (Wittchen et al, 1997).…”
Section: Methods Diagnostic Processmentioning
confidence: 99%
“…Complex networks are characterized by dense local connectivity and sparser long-range connectivity (Barabasi, 2009) that is fractal or selfsimilar at all scales. Many brain disorders appear to be associated with abnormal brain connectivity that may vary between different regions and different scales (Bassett and Bullmore, 2009;Craddock et al, 2009;Noonan et al, 2009). Examples include autism (Belmonte et al, 2004;Noonan et al, 2009), schizophrenia (Raghavendra et al, 2009;Uhlhaas et al, 2008;Whittington, 2008), depression (Li et al, 2008;Sheline et al, 2009) and epilepsy (Douw et al, 2010;Percha et al, 2005).…”
Section: Complex Networkmentioning
confidence: 99%
“…Complex mental disorders such as autism are associated with abnormal brain connectivity that may vary between different regions and different scales (Noonan et al, 2009). Estimation of changes in neural connectivity might be an effective diagnostic biomarker for abnormal connectivity development that leads to ASD behaviors.…”
Section: Infant Brain Development and Autism Spectrum Disordersmentioning
confidence: 99%
“…Task-dependent fMRI studies showed alterations in memory, 45 recognition of face expression, 46 selective attention, 47 cognitive control and executive function, 48 self-and other reflection, 49 self-representation, 50 and motor-response inhibition 51 in patients with ASD. Final conclusions were not yet derived from these studies because of the heterogeneity of paradigms as well as the diagnostic entities and age groups included.…”
Section: Brain Functionmentioning
confidence: 99%